Florida Crop/Pest Management Profile: Atemoya and Sugar Apple - Mark A. Mossler; Olaf Norman Nesheim (EDIS)
This document is CIR 417 one of a series of the Pesticide Information Office, Food Science and Human Nutrition Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: September 2002.